Awareness of process, product, and context integration and interdisciplinary writing performance of undergraduate students - Pedregosa. James V.
With the development in the new General Education Curriculum (GEC) of colleges and universities, underdraduate students are expected to become competent writers in their major field. To achieve this goal, students must acquire two kinds of competency in writing, namely, levels of awareness and performance (Bhatia, 1999:30). However, acquiring the levels of awareness and performance is a big challenge to students engaged in interdisciplinary writing that requires the integration of approaches to writing in the disciplines (Bazeman, 2011:8) prompting this study to develop a theoretical framework of interdisciplinary writing that addresses the challenge. The study aimed to determine the relationships among students awareness of process, product, and context integration and their interdisciplinary writing performance. The participants were 90 undergraduate students enrolled in English 2 (Writing in the discipline) at the time of study and chosen through non-random sampling from where 18 case participants representing the high and low achievers were selected. Another group of participants of 36 undergraduate students who finished the course English 2 (Writing in the Discipline were selected to participate in the needs analysis before the start of the study. The study employed explanatory sequential mixed methods conducted in a non-stock non-profit Catholic university located in Iloilo City, Philippines. The students identified difficulties in interdisciplinary writing were composing notes, going through the steps of the writing process, consulting readers such as teachers and peers, and using graphic organizers as a strategy in interdisciplinary writing. However, based on Spearmans rho, the difficulties in interdisciplinary writing are not significantly related to students awareness of process, product, and context integration because what students perceived to be difficult may not be related to what they know at the beginning and their awareness may change after having learned from the course. The qualitative method that examined the difference between hig and low achieving student participants awareness of process, product, and context integration and interdisciplinary writing performance employing thematic analysis in scrutinizing interview transcripts and portfolio outputs. The results of the quantitative and qualitative analysis were merged leading towards the development of a theoretical framework of interdisciplinary writing of undergraduate students described as one that empowers students to be involved ij the outcome of their writing, gives students opportunity to explore their writing through the interdisciplinary writing tasks, allows students to observe the interrelatedness of process, product, and content; and requires students to submit outputs that demonstrate their interdisciplinary writing performance evaluated through a performance assessment tool.